2020
DOI: 10.3390/ijms21249496
|View full text |Cite
|
Sign up to set email alerts
|

P27 Protects Neurons from Ischemic Damage by Suppressing Oxidative Stress and Increasing Autophagy in the Hippocampus

Abstract: p27Kip1 (p27), a well-known cell regulator, is involved in the regulation of cell death and survival. In the present study, we observed the effects of p27 against oxidative stress induced by H2O2 in HT22 cells and transient ischemia in gerbils. Tat (trans-acting activator of transcription) peptide and p27 fusion proteins were prepared to facilitate delivery into cells and across the blood-brain barrier. The tat-p27 fusion protein, rather than its control protein Control-p27, was delivered intracellularly in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 60 publications
4
22
0
Order By: Relevance
“…In in vivo study, we observed the Tat-SH3GL2, not Control-SH3GL2, could cross the blood-brain barrier and be delivered to the cells in the hippocampal CA1 region. This result is consistent with previous studies that showed that Tat-cargo fusion proteins could cross the membrane and had the potential to be introduced into cells or the hippocampus [17,40,41,43]. In addition, we also observed the neuroprotective effects of Tat-SH3GL2 against 1 mM H 2 O 2 -induced oxidative damage in HT22 cells by WST-1 assay.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In in vivo study, we observed the Tat-SH3GL2, not Control-SH3GL2, could cross the blood-brain barrier and be delivered to the cells in the hippocampal CA1 region. This result is consistent with previous studies that showed that Tat-cargo fusion proteins could cross the membrane and had the potential to be introduced into cells or the hippocampus [17,40,41,43]. In addition, we also observed the neuroprotective effects of Tat-SH3GL2 against 1 mM H 2 O 2 -induced oxidative damage in HT22 cells by WST-1 assay.…”
Section: Discussionsupporting
confidence: 92%
“…Mongolian gerbils (male, 3-month old) were purchased from Japan SLC Inc. (Shizuoka, Japan) and the experimental protocols were approved by the Institutional Animal Care and Use Committee (IACUC) of the Seoul National University, Seoul, Korea (SNU-190516-7). Transient forebrain ischemia in gerbils was induced by occlusion of both the common carotid arteries for 5 min under anesthesia with 2.5% isoflurane (Hana Pharm Co., Ltd., Hwaseong, South Korea), as described in previous studies [40,41]. Complete occlusion of both the arteries was confirmed by observing the central artery of the retina using an ophthalmoscope (HEINE K180 ® , Heine Optotechnik, Herrsching, Germany).…”
Section: Changes Of Sh3gl2 Immunoreactivity In the Gerbil Hippocampusmentioning
confidence: 99%
See 2 more Smart Citations
“…Murine hippocampal HT22 cells were obtained from ATCC (Manassas, VA, USA) and cultured in Dulbecco's modi ed Eagle's medium as described in previous studies [20,21]. Purpurin was dissolved in 200-mM dimethyl sulfoxide (DMSO) and various concentrations of purpurin (1-200 μM) were added to HT22 cells for 60 min.…”
Section: Cell Preparation and Determination Of Cellular Toxicity In Ht22 Cellsmentioning
confidence: 99%